Antibiofilm effects of berberine-loaded chitosan nanoparticles against Candida albicans biofilm. (1st January 2023) - Lin, Quan; Li, Yanxin; Sheng, Maokun; Xu, Jiaman; Xu, Xiaoyan; Lee, Jintae; Tan, Yulong
Abstract: In recent years, the incidence of Candida contamination caused by Candida mastitis has an upward trend, which has a great impact on the hygienic quality of raw milk and dairy products. Candida albicans biofilm plays an important role in fungal infection. It can protect C. albicans from host defense and drug attacks, increasing its drug resistance in the process of infection. Therefore, it has become an urgent problem to find effective means to reduce the biofilm produced by C. albicans and the drug resistance of the strain. In this study, berberine (BBR) was loaded on chitosan nanoparticles (CSNPs) to explore its anti-biofilm effect on C. albicans, and the antifungal mechanism of BBR released from BBR-CSNPs on C. albicans was explored. Results showed that the drug loading content (LC) and the encapsulation efficiency (EE) were the highest when the ratio of CS to BBR was 3:1. Scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM) showed that BBR-CSNPs had better disruption effect on the biofilm of C. albicans than BBR. BBR released from BBR-CSNPs could destroy the cellular structure of C. albicans to achieve antifungal effect. Highlights: Berberine (BBR) was loaded on chitosan nanoparticles (CSNPs) to explore its anti-biofilm effect on Candida albicans. The antifungal mechanism of BBR released from BBR-CSNPs on Candida albicans was explored. This experiment provides a new idea for the treatment of drug resistant strains of Candida albicans.